2014
DOI: 10.5430/jnep.v4n4p74
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of cancer pain management among nurses in a Nigerian tertiary health institution

Abstract: Background: Pain is a symptom of both physical and psychological disorder in patients. Pain may be acute or chronic. Chronic pain can also be the consequence of progressive diseases such as cancer. Cancer pain can be defined as a complex sensation that reflects both damage to the body and the body's response to the damage. Proper pain management is crucial in the overall care of patients. The doctor-patient ratio is still low in Nigeria according to World Health Organization (WHO). 2012, we have 1:3500 doctor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…[13][14][15][16][17] The findings from these studies revealed that nurses had inadequate knowledge about pain assessment and management. [13,[18][19][20] Previous research studies have identified several barriers to adequate pain management in SCD such as: sociocultural factors, the concerns regarding addiction, disbelief of the health care professional and the lack of knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] The findings from these studies revealed that nurses had inadequate knowledge about pain assessment and management. [13,[18][19][20] Previous research studies have identified several barriers to adequate pain management in SCD such as: sociocultural factors, the concerns regarding addiction, disbelief of the health care professional and the lack of knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…According to World Health Organization (WHO), analgesic management of pain which is a three-step approach provides an effective treatment of pain at various levels of severity [17]. This approach involves the use of non-opioid and opioid medications.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the study revealed that more years of experience in cancer nursing were associated with a higher level of understanding. The investigation by Elumelu et al, (2014) disclosed that nurses at Nigerian tertiary health institutions demonstrated insufficient overall knowledge, with only 18% having undergone formal training in cancer pain management. Contributing factors included a lack of structured education, unfamiliarity with opioid administration practices, and an inadequate grasp of pain evaluation and treatment methods.…”
Section: Nurses' Understanding and Disposition Towards Cpmmentioning
confidence: 99%
“…The study conducted by Darawad et al, (2019) in Jordan distinguishes between doctors and nurses, revealing possible deficiencies in knowledge and highlighting the need for fair and extensive education across many healthcare fields. The Nigeria study by Elumelu et al, (2014) and her colleagues demonstrates a dedication to comprehending and tackling obstacles unique to the Nigerian setting. The study emphasizes the importance of treatments designed to suit the local environment.…”
Section: Factors and Obstacles Associated With The Understanding Of Cpmmentioning
confidence: 99%